2015
DOI: 10.1371/journal.pone.0144162
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Accuracy of Whole-Exome Sequencing with Formalin-Fixed Paraffin-Embedded and Fresh Frozen Tissue Samples

Abstract: Formalin fixing with paraffin embedding (FFPE) has been a standard sample preparation method for decades, and archival FFPE samples are still very useful resources. Nonetheless, the use of FFPE samples in cancer genome analysis using next-generation sequencing, which is a powerful technique for the identification of genomic alterations at the nucleotide level, has been challenging due to poor DNA quality and artificial sequence alterations. In this study, we performed whole-exome sequencing of matched frozen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
86
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 15 publications
7
86
0
Order By: Relevance
“…These preserved tissues have the potential to improve our understanding of diseases, especially in oncology where biopsies and resected specimens are routinely maintained in clinical practice. Use of fresh frozen tissue has long been considered the “gold-standard” for molecular assays as proteins and genetic material are preserved in their native state234. However, ice crystal formation is common, creating artifacts that are not seen in FFPE preserved tissues5.…”
mentioning
confidence: 99%
“…These preserved tissues have the potential to improve our understanding of diseases, especially in oncology where biopsies and resected specimens are routinely maintained in clinical practice. Use of fresh frozen tissue has long been considered the “gold-standard” for molecular assays as proteins and genetic material are preserved in their native state234. However, ice crystal formation is common, creating artifacts that are not seen in FFPE preserved tissues5.…”
mentioning
confidence: 99%
“…Our comparison of mutational rates in primary vs persistent/recurrent LSCC needs to be interpreted in this light. However, several recent studies have demonstrated high (ie, > 90%) concordance rates in detection of SNVs and CNVs in coding genomic regions between matched fresh‐frozen and FFPE tumor samples . In addition, comparison of amplicon‐based, targeted exome sequencing to TCGA dataset is a well‐established practice in the HNSCC literature .…”
Section: Discussionmentioning
confidence: 99%
“…However, several recent studies have demonstrated high (ie, > 90%) concordance rates in detection of SNVs and CNVs in coding genomic regions between matched freshfrozen and FFPE tumor samples. [28][29][30] In addition, comparison of amplicon-based, targeted exome sequencing to TCGA dataset is a well-established practice in the HNSCC literature. 11,13 Thus, we believe that these differences in DNA sequencing methodology do not significantly diminish the validity of our comparisons and conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that formalin fixation causes DNA denaturation, base alteration and production of sequence artefact (Douglas and Rogers 1998;Oh et al 2015). Gallegos Ruiz and colleagues (2007) have observed mutational artefacts in epidermal growth factor receptor (EGFR) gene resulting from formalin fixation and paraffin embedding of lung tissue sample.…”
Section: Limitations In Tissue Processingmentioning
confidence: 99%
“…Therefore, formalin-processed tissue specimens might not accurately reflect the genetic alterations present in the tumour tissue. The use of fresh frozen tissue for processing might overcome these limitations, but it is restricted by logistic issues such as availability of liquid nitrogen and requirement of specialised equipment for processing and storage of frozen tissue (Budczies et al 2011;Oh et al 2015).…”
Section: Limitations In Tissue Processingmentioning
confidence: 99%